Android Based Heart Rate Detection Tools with Arduino Nano - Hidayatul Muttaqin; Ita Arfyanti; Wahyuni (TEPIAN, 2021)
Android-based Heart Rate Detector Using an Android-Based Fingerprint Using Arduino Nano at Midwife Dwi Inggrini's Maternity Clinic with the hope of helping and simplifying the medical team in checking the heart rate of pregnant women without having to carry devices that are not portable, improving services and errors due to blackouts PLN electricity. The software development method used is the prototype method which includes data collection, design, prototyping, the testing phase by conducting Black Box and White Box testing. To access this tool the user must first connect the bluetooth android device with bluetooth HC-05 on the Arduino device, after the two Bluetooth devices are connected.